Developing a workplace lactation promotion model in Indonesia using Delphi technique - Ray Wagiu Basrowi; Sudigdo Sastroasmoro; Astrid W Sulistomo; Saptawati Bardosono; Aryono Hendarto; Dewi S Soemarko; Ali Sungkar; Levina Chandra Khoe; Yvan Vandenplas (BMC, 2018)
Abstract Background Working mothers have a higher risk to terminate breastfeeding earlier than stay-at-home mothers. Researchers reported that support from the workplace by creating lactation facilities and develop supportive programs are necessary to increase the success of exclusive breastfeeding. The aim was to achieve expert consensus on developing a workplace-based lactation promotion model. Methods A three-round online survey using Delphi approach was conducted to reach consensus on to the development of a lactation program at a workplace. Results Twenty-two experts from Indonesian health authority, community medicine, child health and obstetrics were invited to join the Delphi study; 15 (68.2%) enrolled in the first round. The response rate in the second and third round was 80.0% (12/15) and 86.7% (13/15), respectively. The first round categorized the workplace-based promotion model into seven dimensions, i.e. policy and regulation, facility, education material, target participants, promotion approach, human resources, and time. In the final round, "maternity leave of 3-6 months" (median (Q1;Q3):2 (1, 4)) and "employees have the right to breast-pumping every 3 hours" (median (Q1;Q3):3 (2, 4)) ranked as the two most important indicators regarding policy and regulation. A dedicated lactation room (median (Q1;Q3):1 (1)) is the highest ranked indicator regarding facility dimension. Regarding education materials, benefits of breast milk for babies ranked as the highest indicator while for the education and delivering methods dimensions, social media and interactive counseling were two highest ranked indicators. The top management in the company and lactation counselor are the two highest-ranked indicators in human resources dimension. Conclusion In the view of experts, involvement of a dedicated policy maker in the company, a workplace-based lactation counselor, regular promotion with interactive education and dedicated facilities are necessary to develop an effective workplace-based lactation promotion model.